Codependence of Bone Morphogenetic Protein Receptor 2 and Transforming Growth Factor-β in Elastic Fiber Assembly and Its Perturbation in Pulmonary Arterial Hypertension. Issue 8 (August 2017) - Tojais, Nancy F.; Cao, Aiqin; Lai, Ying-Ju; Wang, Lingli; Chen, Pin-I; Alcazar, Miguel A. Alejandre; de Jesus Perez, Vinicio A.; Hopper, Rachel K.; Rhodes, Christopher J.; Bill, Matthew A.; Sakai, Lynn Y.; Rabinovitch, Marlene
Abstract : Objective—: We determined in patients with pulmonary arterial (PA) hypertension (PAH) whether in addition to increased production of elastase by PA smooth muscle cells previously reported, PA elastic fibers are susceptible to degradation because of their abnormal assembly. Approach and Results—: Fibrillin-1 and elastin are the major components of elastic fibers, and fibrillin-1 binds bone morphogenetic proteins (BMPs) and the large latent complex of transforming growth factor-β1 (TGFβ1). Thus, we considered whether BMPs like TGFβ1 contribute to elastic fiber assembly and whether this process is perturbed in PAH particularly when the BMP receptor, BMPR2, is mutant. We also assessed whether in mice with Bmpr2/1a compound heterozygosity, elastic fibers are susceptible to degradation. In PA smooth muscle cells and adventitial fibroblasts, TGFβ1 increased elastin mRNA, but the elevation in elastin protein was dependent on BMPR2; TGFβ1 and BMP4, via BMPR2, increased extracellular accumulation of fibrillin-1. Both BMP4- and TGFβ1-stimulated elastic fiber assembly was impaired in idiopathic (I) PAH-PA adventitial fibroblast versus control cells, particularly those with hereditary (H) PAH and a BMPR2 mutation. This was related to profound reductions in elastin and fibrillin-1 mRNA. Elastin protein was increased in IPAH PA adventitial fibroblast by TGFβ1 but only minimally so in BMPR2 mutant cells. Fibrillin-1 protein increased only modestly in IPAH or HPAH PA adventitial fibroblasts stimulated with BMP4 or TGFβ1. In Bmpr2/1a heterozygote mice, reduced PA fibrillin-1 was associated with elastic fiber susceptibility to degradation and more severe pulmonary hypertension. Conclusions—: Disrupting BMPR2 impairs TGFβ1- and BMP4-mediated elastic fiber assembly and is of pathophysiologic significance in PAH. Abstract : Supplemental Digital Content is available in the text.